THE EFFECT OF PSYCHOLOGICAL INTERVENTION ON PERCEIVED PAIN IN CHILDREN UNDERGOING VENIPUNCTURE - Sikorova, Lucie; Hrazdilova, Petra (Biomedical papers, 2011)
Aims: The main objective of the study was to determine the effect of structured psychological intervention on the level of perceived pain in children undergoing venipuncture. A second goal was to investigate how pain behavior during venipuncture is affected by age, sex, previous number of venipunctures, the presence of parents during the procedure and reason for the venipuncture.Methods: Children with indications for venipuncture aged 5-10 years, were randomly divided into a control group and an intervention group. The control group was prepared for the venipuncture routinely. Children in the intervention group were prepared according to prior structured psychological consultation. Perceived pain levels were assessed by the CHEOPS scale and the self report Wong and Baker faces pain rating scale.Results: A significant difference in evaluated pain between the intervention group and the control group was found. The psychological intervention carried out by a nurse proved to lower pain levels from venipuncture as measured by the CHEOPS scale and evaluated using the self-report scale. A greater level of pain was found in children in the age group 5-7 years, in children where peripheral venous catheter was introduced and in children where the parents were present. Special consultation with the child one day before venipuncture reduced pain levels, especially in children below the age-category mentioned. Consultation should be part of the standard of care for children with indications for venipuncture.
Keywords: Pain Measurement/Venipucture/Randomized studies/Child/Nonpharmacological Interventions